KEMAMPUAN KOMUNIKASI DAN BERPIKIR KREATIF PESERTA DIDIK PADA MATERI ORGANISASI KEHIDUPAN MELALUI PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) - Dimas Wahyu Satrya Romadhon; Moh Riswandha Imawan (Universitas Muhammadiyah Surabaya, 2024)
21st century education encourages students to master four things: communication, collaboration, creativity, and problem solving. This study aims to: (1) determine the development of students' creative thinking skills by using the PjBL model; (2) determine the development of students' oral communication by applying the PjBL model; (3) describe the learning implementation of the PjBL model; (4) describe students' responses to the PjBL model learning model. This type of research is Pre-Experimental with One Group Pretest and Posttest Design. The research sample was VII A students of SMP Muhammadiyah 3 Surabaya based on purposive sampling technique. Data collection techniques using tests, questionnaires and observations. Data analysis uses descriptive and statistical analysis with n-gain and T-test. based on the results of the study concluded: (1) there is a development of students' creative thinking skills after the application of the PjBL model with an N-Gain value of 0.68 with a “medium” category; (2) there is a development of students' oral communication skills after the application of the PjBL model indicated by an average value of 90 in the “very good” category; (3) learning with the PjBL model is carried out with the mode of “Very Good” criteria; (4) implementation with the model gets a good response from students with a percentage of 95.7%.